Aspects of the ecology and the behaviour of the Leopard Panthera pardus in the Kalahari desert - J du P Bothma; E. A. N le Riche (Koedoe: African Protected Area Conservation and Science, 1984)
Tracking in sand revealed data on hunting and kill rates, range, movements, activity, cover and water use, reproduction and interactions with other carnivores, by the leopard Panthera pardus in the Kalahari Gemsbok National Park. For leopards in the interior, 812,5 km of tracks were followed for 54 days, and 205,1 km for 15 days for females with cubs. In the Nossob riverbed 30,2 km of tracks were folowed in eight days. Medium-sized mammals featured prominently in the diet of all leopards, with prey used influenced by habitat type. Leopards in the interior moved greater distances than those in the Nossob riverbed. Leopards rested frequently at the onset and end of activity and used dense vegetation and aardvark Orycteropus afer and porcupine Hystrix africaeaustralis burrows as daytime cover. Leopards are independent of water, and females apparently have no definite breeding season. Lions Panthera leo dominate leopards, but the outcome of leopard/spotted hyaena Crocuta crocuta encounters depend on the size of the leopard and the number of hyaenas in the pack. Leopards in the Kalahari Desert are opportunists which occupy this harsh envi- ronment successfully.